Near-real-time forests disturbance monitoring: Nota de investigación - Tanase, Mihai; Lamelas Gracia, María Teresa; García Martín, Alberto (Geographicalia, 2022)
Short Communication about the project "Near-real-time forests disturbance monitoring" led by Mihai Tanase and supported by the Spanish Ministry of Science and Innovation (PID2020-114062RA-I00). The project has two objectives: 1) appraise spatial-temporal trends in forest disturbance by creating an open access national database spanning the last four decades from historical EO datasets and 2) develop a novel near-real-time integrated forest monitoring framework based on the integration of low-frequency high-resolution (
Keywords: Forest ecosystem dynamics; Remote sensing, up-to-date information; Spain